Serum Antidiuretic Hormone Level in Nocturnal Enuretic School Children in a Tertiary Care Hospital in Bangladesh: A Cross‐Sectional Study - Jannatul Fardous; Anjuman Ara; Md. Iqbal Hossain; Asma Labony; Tanjila Afrin; Rezwana Ashraf; Reaz Uddin; Habiba Jesmin; Md. Kabir Alam; Mohammad Ashraful Amin; Anwar Hossain Khan; Zahid Hasan Khan (Health Science Reports)
ABSTRACT Background and Aims Primary nocturnal enuresis (PNE) is a common pediatric condition characterized by involuntary nighttime bed wetting. Primary monosymptomatic nocturnal enuresis (PMNE) is associated with altered antidiuretic hormone (ADH) secretion and lacks lower urinary tract symptoms. This study aimed to compare serum ADH levels between children with PMNE and a comparison group to explore its potential role in the pathophysiology of PMNE. Methods This cross‐sectional study included 40 children aged 6–15 years with PMNE and 40 age‐matched children without enuresis (comparison group) attending the Pediatric Nephrology Outpatient Department at the National Institute of Kidney Diseases and Urology (NIKDU) from January 2022 to July 2023. Blood samples and other clinical information along with laboratory investigation are done to ensure inclusion and exclusion criteria. Fasting serum ADH level, a competitive immunoassay was done with the Arg‐ Vasopressin ELISA kit. Relevant clinical and demographic data were analyzed using Student's t‐test for continuous variables and Chi‐square/Fisher's exact tests for categorical variables. Results The mean age of participants was 8.82 ± 2.71 years in the PMNE group and 9.01 ± 2.54 years in the comparison group (p = 0.760). There was no significant association between sex and PMNE (p = 0.370). Children with PMNE exhibited significantly lower serum ADH levels compared to the comparison group (p < 0.05). Additionally, children with more frequent enuretic episodes demonstrated a trend of lower ADH levels (p < 0.05). Conclusion This study provides evidence of a significant association between decreased diurnal serum ADH levels and PNE in children. These findings contribute to a better understanding of the pathophysiology of PNE and suggest potential avenues for novel treatment strategies, emphasizing the importance of evaluating ADH levels in PNE management.